Ferrocene‐Induced Perpetual Recovery on All Elemental Defects in Perovskite Solar Cells. (20th October 2021) - Chang, Qing; Wang, Fangfang; Xu, Wenxin; Wang, Aifei; Liu, You; Wang, Juangan; Yun, Yikai; Gao, Song; Xiao, Kang; Zhang, Liangliang; Wang, Lin; Wang, Jianpu; et al.
Abstract: Lead halide perovskites always emerge complex interactions among different elemental ions, which lead to multiple intrinsic imperfections. Elemental defects, such as amine, Pb, and I vacancies at A‐, B‐, and X‐sites, are main issues to deteriorate perovskite solar cells (PSCs). Unfortunately, most previous passivators can only temporarily fix partial inactive vacancies as sacrificial agents. Herein, we propose a recovery agent, ferrocene (Fc), which can form a one‐dimensional perovskite with adequate steric cavities and suitable dissociation energy to recover all elemental defects back to active light‐harvesting perovskites, and regenerate Fc itself meanwhile. Based on this perpetual chain‐reaction cycle, corresponding PSCs maintain >10 000‐hour lifetime in inert condition and >1000‐hour durabilities under various extreme environments, including continuous 85 °C heating, 50 % relative humidity wetting, and 1‐sun light soaking. Abstract : Towards stable solar cells, ferrocene as a perpetual recovering agent has been developed to fix all elemental defects in ABX3 perovskite by a chain‐reaction cycle. The ferrocene cations can form a 1D perovskite structure which has suitable dissociation energy to convert back to light‐harvesting 3D perovskite and reactivate its photovoltaic performance. Based on this recovering agent, perovskite solar cell can achieve >10 000 h lifetime.